Conflicts over compensation of expropriation. The case of farmland in France. - Romain Melot (European Regional Science Association (ERSA), 2012)
From a legal sociology perspective, the research presented here aims to show that the legal claims strategies in matters of land expropriation cannot be satisfactorily explained without taking into account observable judicial practices at a local level. Indeed, the characteristics of real estate assets, both their private use and public management, are essential elements which explain why within the framework of public use projects, either negotiated settlement or, on the contrary, referral to court, is prescribed as the relevant context for determining compensation. This review of the current state of the law concerns two aspects which are different but both strongly nested in local land systems. First, we find the situation of individuals with regard to the rights they possess over real estate assets. Indeed, when we speak about land expropriation, it is above all in relation to the stakes behind owners' property rights. But the law also provides for the protection of the rights of non-owners, such as lease-holders endowed with land-use rights whose business interests may be adversely affected by land development projects. As discussed further in the paper, this situation is unavoidable when dealing with the expropriation of land supporting economic activity in which land leasing is a widespread practice, such as agriculture in France. In terms of public law, it is essential to take into account local judicial practices, not only to understand the structure of disputes between condemnor and condemnee, but also to explain the decision to go to court. Regulatory practices in matters of urban development projects clearly influence the nature of building permits associated with developed and undeveloped sites. The type of zoning, the building code for construction and extension of existing structures and building standards for public infrastructure projects (land reclamation, roadbuilding, electricity, water…) are all factors which directly influence land value estimates. It seems reasonable, then, to posit the idea that land disputes often directly reflect local urban building codes and, consequently, policies implemented by local authorities. We wish to further underline the fact that eminent domain is very often exercised within the context not of large infrastructure projects but of ordinary urban development. Recourse to `public use' prerogatives is thus used as a complement to urban planning policies.
Keywords: 330